Engineering Students’ Perceived Usefulness and Attitudes toward VocBlast in Learning Specialized Vocabulary - Zuraina, Ali; Nurul Nadia, Mohammad (UiTM Pahang, 2016)
The current study attempts to investigate the perceived usefulness and attitudes of using VocBlast between genders. The study employed a survey method in collecting its data among 129 students studying at a higher education level in the East Coast of Malaysia. The results from the study revealed that both male and female students did not differ in their perceived usefulness and attitudes when playing VocBlast. This is due to the fact that the app is still new to them, and, thus more time is required to make them familiar with the games in the app.